Renal function outcomes in living kidney donors in a transplant center in Colombia - Rodolfo Torres; Maricely Reina; Camilo Montero; Andres Tunjano; David Andrade; Valeria Mancera; Maria Amaya; Lizeth Arias; Laura Castellanos; Valentina Vanegas (SAGE Open Medicine)
Introduction: Living kidney donation is currently low in Colombia, and this is associated with the lack of knowledge of the risks and renal function outcomes of potential donors; there are no studies that evaluate these outcomes. The objective of this study is to evaluate the outcomes of renal function, the incidence of metabolic diseases, arterial hypertension, as well as the finding of albuminuria and/or proteinuria in living kidney donors with a 2-year follow-up post donation. Methods: Observational study in living kidney donor patients, in which renal function outcomes were evaluated between the predonation period and up to 24 months postdonation. Results: Ninety-one patients were included, with a median predonation glomerular filtration rate of 98 ml/min/1.73 m 2 , interquartile range (90.5–109), and 24-month postdonation of 66.3 ml/min/1.73 m 2 interquartile range (57.9–75). A total of 60.26% of the population was in stage 2 at the end of follow-up and no patient had a glomerular filtration rate less than 30 ml/min/1.73 m 2 or required renal support therapy. Conclusion: A living donor evaluation process based on risk factor stratification and adequate assessment of renal function was found to generate safe renal function outcomes both in the perioperative period and in medium- and long-term follow-up.